Reduction of reconciliation errors in chronic pediatric patients through an educational strategy - Claudio González; Gabriela González; José Cristian Plaza-Plaza; María Inés Godoy; Marcela Cárcamo; Cecilia Rojas (Elsevier, 2021)
Background: Medication reconciliation errors, also known as unintentional discrepancies, are frequent during admission, especially in chronic patients, and have impact in safety. Educational interventions can be a reduction strategy. Material and Methods: Quasi-experimental study, before-after design. Participants were chronic patients admitted into hospitalization services. Medication reconciliation was conducted at admission. The intervention consisted of a training to each prescribing physician with study contents and printed educational material. To study the association between intervention and change of frequency of unintentional discrepancies was made a logistic regression model, adjusting for selected variables. Results: A sample of 54 patients was studied in each stage. In the first stage it was observed that 42,6% of patients had at least one unintentional discrepancy. After intervention the proportion of patients with at least one unintentional discrepancy decreased to 24,1% (P = ,041). In both stages, omission was the main category of unintentional discrepancy. The significant reduction after the intervention is maintained by controlling for variables such as emergency admission and pre-admission service. Conclusions: Incidence of unintentional discrepancies in admission is high in chronic hospitalised patients and can be reduced through an educative strategy. Resumen: Introducción: Los errores de conciliación, o discrepancias no justificadas (DNJ), son frecuentes durante la admisión a hospitalización de los pacientes pediátricos crónicos y tienen impacto en la seguridad. Las intervenciones educativas podrían ser una estrategia para su reducción. Pacientes y métodos: Estudio cuasi - experimental, diseño antes - después en pacientes crónicos pediátricos. Se realizó en una primera etapa, la conciliación de los medicamentos prescritos tras la admisión hospitalaria, y se calculó la frecuencia de pacientes con al menos una DNJ. La intervención educativa consistió en una formación a cada médico con los conceptos de conciliación de la medicación, los resultados de la primera etapa y una infografía que se distribuyó en las áreas de prescripción. En una segunda etapa, se procedió de la misma forma que en la primera etapa. Para estudiar la asociación entre la intervención y el cambio en la frecuencia de DNJ se realizó un modelo de regresión logística, ajustando por covariables. Se utilizó un nivel de significación del 5%. Resultados: Se estudió una muestra de 54 pacientes en cada etapa. En la primera, un 42,6% de los pacientes presentó al menos una DNJ. Tras la intervención la proporción se redujo a un 24,1% (P = ,041). En ambas etapas la omisión fue la principal categoría de DNJ. La reducción significativa tras la intervención se mantuvo al controlar por variables como ingreso por urgencia y servicio de preadmisión. Conclusiones: La frecuencia de DNJ en la admisión es alta en pacientes crónicos hospitalizados y puede ser reducida mediante una estrategia educativa.